Analisis ukuran perusahaan, keputusan pendanaan, dan profitabilitas terhadap nilai perusahaan di bursa efek Indonesia - Sanjaya, Heriyani; Permata Husda, Anggun (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
In general, companies have a goal to increase the wealth of company owners or shareholders. But in the long term, companies have a goal to optimize the value of the company. Optimizing the value of the company is done in order to invite investors to invest in the company. The purpose of this research is to determine the effect of firm size, funding decisions, and profitability on the firm value of the food and beverage sub-sector companies listed on the Indonesia Stock Exchange. This study uses a non-probability sampling method, namely the purposive sampling method and there are 13 companies that have met the sample criteria determined by the researcher. The results of hypothesis testing using t-test indicate that firm size has a significant partial effect on firm value with a significance level of 0.042 <0.05. Funding decisions have no significant partial effect on firm value with a significance level of 0.661 > 0.05. Profitability partially has a significant effect on firm value with a significance level of 0.000 <0.05. Meanwhile, the results of the F test indicate that firm size, funding decisions, and profitability have a simultaneous positive and significant effect on firm value with a significance level of 0.000 <0.05.